2021
DOI: 10.20396/bjos.v20i00.8661654
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rs6667202 SNP on Interleukin-10 levels in the gingival fluid of patients with periodontitis grade C

Abstract: Grade C periodontitis in youngers is characterized by a severe form of periodontitis, and IL10 rs6667202 single nucleotide polymorphism (SNP) has been described as an important feature in this disease etiology. Aim: This study aimed to evaluate, in vivo, the functionality of IL10 rs6667202 SNP on IL-10 gingival fluid levels. Methods: Thirty patients with Perio4C were selected, 15 with the IL10 AA genotype (rs6667202) and 15 with AC/CC genotypes. The gingival fluid was collected from two sites with probing dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Integrating different factors that participate in the etiopathogenesis of Perio4C, Casarin et al, 2010 showed a lower level of IL‐10 in the GCF of individuals with Perio4C while detected a higher concentration of Aa and reduced concentration of immunoglobulin G (IgG) against this pathogen 43 . More recently, a preliminary in vivo study has shown that rs6667202 SNP leads to a decrease in IL‐10 production only in deep pockets of Perio4C patients, where a mature and dysbiotic biofilm is instigating the host response 19 . Teles et al, 2010 correlated bacterial species of the red complex with a higher expression of biomarkers (IL‐1β, IL‐8, and MMP‐8) in GCF, while species of the yellow and purple complex were associated only with MMP‐8.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Integrating different factors that participate in the etiopathogenesis of Perio4C, Casarin et al, 2010 showed a lower level of IL‐10 in the GCF of individuals with Perio4C while detected a higher concentration of Aa and reduced concentration of immunoglobulin G (IgG) against this pathogen 43 . More recently, a preliminary in vivo study has shown that rs6667202 SNP leads to a decrease in IL‐10 production only in deep pockets of Perio4C patients, where a mature and dysbiotic biofilm is instigating the host response 19 . Teles et al, 2010 correlated bacterial species of the red complex with a higher expression of biomarkers (IL‐1β, IL‐8, and MMP‐8) in GCF, while species of the yellow and purple complex were associated only with MMP‐8.…”
Section: Discussionmentioning
confidence: 99%
“…12 patients, where a mature and dysbiotic biofilm is instigating the host response. 19 Teles et al, 2010 correlated bacterial species of the red complex with a higher expression of biomarkers (IL-1β, IL-8, and MMP-8) in GCF, while species of the yellow and purple complex were associated only with MMP-8. In addition, even the healthy sites of patients with periodontitis had higher levels of IL-1β and IL-8 and periodontal pathogens than the PH group, showing distinct associations between the host's immune response and microbial complexes.…”
Section: Rs6667202 Modulates Hgfs Il-10 Response After Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…New evidence suggests a potential role of host response in establishing dysbiosis and inflammation as a determinant factor in periodontitis pathogenesis (Van Dyke, Bartold, & Reynolds, 2020). In GAgP subjects, a vast number of studies suggested that genetic aspects could determine cytokine profile (Schaefer, 2018;Stolf et al, 2021;Taiete et al, 2019), what can potentially impact the subgingival environment and drives colonization. This comprehension of those interfering with the microbial community and treatment response is of great interest and should be further considered.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the rs6667202 SNP, a recent in vivo preliminary study indicated its potential functional role, with lower interleukin 10 (IL-10) production in the crevicular fluid (16). Once IL-10 presents regulatory and anti-inflammatory properties, reducing the expression of proinflammatory cytokines, such as interleukin 1β (IL-1β) and tumoral necrosis factor α (TNF-α) (17,18), the higher frequency of rs6667202 SNP in Perio4C population can be explained.…”
Section: Introductionmentioning
confidence: 99%